Consistent Flexibility: Enforcement of Fiscal Rules Through Political Incentives - Eckhard Janeba; Valerio Dotti (ZBW - Leibniz Information Centre for Economics, 2021)
We study a fiscal policy model in which the government is present-biased, leading to an excessive public deficit. An optimally designed fiscal rule needs to trade off the benefit of committing the government to not overspend against the benefit of granting it flexibility to react to shocks to tax revenues. Unlike prior work, we characterize a rule that is enforced through political incentives: the punishment for a violation of the rule consists in a reduction of the politician's payoff from being in office during the following period. We show that the optimal fiscal rule prescribes a zero structural deficit and only partially accounts for revenue shocks. Moreover - and somewhat surprising - a government with a stronger ex ante deficit bias should be granted a higher degree of flexibility. Flexibility leads to more rather than less fiscal discipline because the punishment for a rule violation is less driven by luck and more dependent on actual policy choices. Thus a trade-off between fiscal discipline and fiscal rule flexibility, as often claimed in the context of the EU's Stability and Growth Pact, does not typically exist in our model.
Keywords: H2; 330